(606) A Multiple-Regression Analysis of International Trade Flows - Its Setup, and Main Results تحليل الانحدار المتعدد لتدفقات التجارة الدولية - إعداده ونتائجه الرئيسية. - Linnemann, Hans; Youssef, Mary N. (INP, 2024)
Since the late 1940s, economists have increasingly focused on the economic development of less-advanced countries, recognizing its significance both academically and practically. This renewed interest has also influenced related fields, such as international trade, particularly concerning developing nations. While much of the existing research is qualitative, analyzing the intricate relationships between economic growth and world trade, the current study takes a predominantly quantitative approach. It aims to explain the value of economic growth and development using average economic relations, building upon earlier research from the Netherlands Economic Institute.